Legality of Commercial Parody Merchandise Without the Authorization of the Owner of the Parodied Brand Based on the Perspective of the MIG Act - Mustofa , Rabindra Aldyan Bintang; Waspiah, Waspiah (Semarang State University Undergraduate Law and Society Review, 2025)
This study examines the criminal liability of corporations as perpetrators of environmental crimes in Indonesia. With increasing industrial activities contributing to environmental degradation, holding corporations accountable under criminal law is essential to deter future violations and promote sustainable business practices. This research analyzes the existing legal framework, judicial practices, and challenges in enforcing corporate criminal responsibility for environmental damage. Through a doctrinal and case law approach, the study highlights gaps in regulation, inconsistencies in court rulings, and the difficulty of attributing mens rea (criminal intent) to corporate entities. The contribution of this study lies in proposing clearer legal criteria and enforcement mechanisms to strengthen corporate accountability for environmental harm. It emphasizes the need for comprehensive legislation that balances economic growth with environmental protection, ensuring that corporations cannot evade liability due to complex organizational structures. This research is relevant for policymakers, legal practitioners, and environmental advocates seeking effective solutions to environmental crimes committed by corporations in Indonesia.